Biocompatible and Biodegradable Light‐Emitting Materials and Devices. Issue 2 (18th May 2021) - Kong, Deying; Zhang, Kaiyuan; Tian, Jingjing; Yin, Lan; Sheng, Xing
Abstract: Implantable devices with desirable biocompatibility and even degradability are of significant interest to biomedical communities. Biologically safe and resorbable electronic materials and devices have been extensively explored, and numerous biodegradable optical sensors, detectors, and waveguides have also been successfully demonstrated. However, biocompatible and degradable optical emitters, especially electrically driven ones, are relatively underexplored. This article provides an overview on the recent progress in the development of biocompatible and biodegradable light‐emitting materials and devices. First, an introduction on molecular dyes, proteins, and inorganic particles with photoluminescence is provided. Subsequently, material systems with unusual optical properties including sonoluminescence, chemiluminescence, and bioluminescence are highlighted. Finally, electroluminescent materials and device with potential for fully biodegradation are emphasized upon. Upon success, it is envisioned that these biodegradable light‐emitting materials and devices would provide effective and unique capabilities in broad biomedical applications from biological sensing and modulation to clinical diagnostics and therapy. Abstract : Biocompatible and biodegradable light‐emitting materials and devices are reviewed in this article. Their materials composition, device structures, performance, and emerging application in biomedical fields are highlighted. Paths toward fully bioresorbable, electrically driven light‐emitting devices are discussed.